2019
DOI: 10.1097/shk.0000000000001442
|View full text |Cite
|
Sign up to set email alerts
|

Venous-to-Arterial Carbon Dioxide Partial Pressure Difference: Predictor of Septic Patient Prognosis Depending on Central Venous Oxygen Saturation

Abstract: This study aimed to assess the viability of using the venous-to-arterial carbon dioxide partial pressure difference (P(v–a)CO2) to predict clinical worsening of septic shock, depending on central venous oxygen saturation (ScvO2). The prospective, observational, multicentric study conducted in three intensive care units (ICUs) included all patients with a septic shock episode during the first 6 h, with 122 patients assessed. Clinical worsening was defined as an increase of sequential organ failure assessment (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…To determine diagnostic values, we assessed ROC curves and areas under the receiver operating characteristic curves (AUCs) to discriminate SIMD from sepsis and predict 28day mortality. The best cut-off value was identified as serum Lcn10 levels present the greatest total of sensitivity and specificity by the Youden index (J) method [20]. The positive predictive value (PPV) and negative predictive value (NPV) were calculated as follows:…”
Section: Discussionmentioning
confidence: 99%
“…To determine diagnostic values, we assessed ROC curves and areas under the receiver operating characteristic curves (AUCs) to discriminate SIMD from sepsis and predict 28day mortality. The best cut-off value was identified as serum Lcn10 levels present the greatest total of sensitivity and specificity by the Youden index (J) method [20]. The positive predictive value (PPV) and negative predictive value (NPV) were calculated as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, serum lactate concentration at T6 was not associated with ΔSOFA ≥ 1. Interestingly, we previously showed that lactate clearance was similar in patients with tissue hypoxia with or without achieving ΔSOFA ≥ 1 20 . Finally, the usefulness of the serum lactate level was more suitable in association with another tissue hypoxia factor 38 .…”
Section: Discussionmentioning
confidence: 90%
“…The data were gathered upon ICU admission (T0), 6 hours after admission (T6), 12 hours after (T12), 24 hours after (T24), 48 hours after (T48) and 72 hours after (T72). Hemodynamic variables were included as in our previous study 20 . The Simpli ed Acute Physiology Score (SAPS II) was collected upon admission 21 .…”
Section: Measurements and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical example for this could be in the event of hyperventilation in response to metabolic acidosis secondary to tissue hypoxia 21 in patients with intact respiratory drive, which could acutely affect the ∆PCO 2 , causing even higher values than the low flow state of tissue hypoxia itself, leading to misinterpretation of patient prognosis. 3 The interpretation of this parameter becomes particularly tricky when narrow cut-off values of ∆PCO 2 or similar indices, for example, the ∆PCO 2 /∆tO 2 ratio, are used. The ∆PCO 2 /∆tO 2 ratio has been shown to be a good marker for global anaerobic metabolism and fluid responsiveness.…”
Section: Discussionmentioning
confidence: 99%